Fundamentals of electric circuits / Charles K. Alexander and Matthew N.O. Sadiku. - Alexander, Charles K., author; Sadiku, Matthew N. O., author (New York, New York : McGraw-Hill Education, 2017)
"Alexander and Sadiku's sixth edition of Fundamentals of Electric Circuits continues in the spirit of its successful previous editions, with the objective of presenting circuit analysis in a manner that is clearer, more interesting, and easier to understand than other, more traditional texts. Students are introduced to the sound, six-step problem solving methodology in chapter one, and are consistently made to apply and practice these steps in practice problems and homework problems throughout the text."--Publisher's website
Part 1. DC Circuits : -- 1. Basic Concepts -- 2. Basic Laws -- 3. Methods of Analysis -- 4. Circuit Theorems -- 5. Operational Amplifiers -- 6. Capacitors and Inductors -- 7. FirstOrder Circuits -- 8. SecondOrder Circuits -- Part 2. AC Circuits : -- 9. Sinusoids and Phasors -- 10. Sinusoidal SteadyState Analysis -- 11. AC Power Analysis -- 12. ThreePhase Circuits -- 13. Magnetically Coupled Circuits -- 14. Frequency Response -- Part 3. Advanced Circuit Analysis : -- 15. Introduction to the Laplace Transform -- 16. Applications of the Laplace Transform -- 17. The Fourier Series -- 18. Fourier Transform -- 19. TwoPort Networks
Includes bibliographical references and index.
In English text.
Keywords: Electric circuits